The Urgency of Sociolinguistics in Arabic Language Education: Strengthening Social Awareness and Language Proficiency Through Effective Educational Management - Saidatul azizah; Hikmatuddiniah; M. Syukron Maksum; Nur Hasanah (Al-Qalam Institue, 2025)
This study examines the urgency of integrating sociolinguistic principles into Arabic language learning to enhance social awareness, contextual understanding, and communicative competence among eighth-grade MTs students. Many learners struggle to adapt formal classroom Arabic to everyday communication, particularly in navigating dialectal variation, vocabulary choice, and Islamic communication norms. Addressing these challenges, the research aims to explore how sociolinguistics can be embedded within the Arabic curriculum to support more natural and context-appropriate speaking skills. Using a descriptive qualitative approach, data were collected through literature analysis, classroom observations, and semi-structured interviews with teachers and students. The findings reveal that sociolinguistic-based instruction enriches students’ maharah kalam, reduces speaking anxiety, and strengthens social interaction by enabling them to adjust language use to different contexts. These results imply the need for a more